The creation, content and use of urban tree strategies by English local governments. Issue 4 (2nd October 2022) - Hand, Kathryn L.; Rix, Harriet; Stokes, Jon; Doick, Kieron J.
ABSTRACT: Urban tree management in England is led by local governments who may describe their policies and practices in a publicly accessible document, termed an urban tree strategy. To understand the role of such documents in urban tree management, this research investigated their prevalence, production, content and use in England. Concurrently, to understand the "life-cycle" of a tree strategy - the processes underlying the production and use of strategies - we conducted semi-structured interviews with 26 local governments. We found 143 of 353 (41%) English local governments had a publicly accessible urban tree strategy. We conducted a review of the content of half (72) of these strategies. We found tree strategies to be highly variable but diverged into two main forms, the 'strategy' form and the 'policy' form. The former is a holistic and forward-looking document, the latter a focused document centred on essential management and legislated duties. The interviews highlighted lack of time, knowledge, money, and/or political buy-in as barriers to strategy production. The variability in the existence and content of strategies could lead to differing urban forest management practices across England, which are not in line with recent national environmental objectives and recommended guidance.